Sebuah RASAKAN PEDANGKU! STRATEGI DAN PENILAIAN KUALITAS PELOKALAN DALAM DESKRIPSI SKILL DI TORAM ONLINE MMORPG - Ryo Adi Buwono; Robith Khoiril Umam (Universitas Putera Batam, 2026)
This research investigates the localization strategies and quality of combat skill descriptions in Toram Online MMORPG from English to Bahasa Indonesia. The goals of the study are to reveal the type of description performed by Toram Online MMORPG in describing the combat skills and to reveal the localization strategies and its quality in translating the skill description in Toram Online MMORPG. The study employed a descriptive qualitative method, collecting textual and visual data from the game. The analysis utilizes Gardner’s (1983) theory for description types, alongside Purnomo’s (2019, 2025) frameworks for spatialization strategies and Ludic Localization Quality Assessment (LQA). The findings reveal that Faithful Description (161 data) is the dominant type, indicating a priority on technical accuracy. Regarding strategies, the translator predominantly employed Mediation (226 data) and Retention (138 data) to balance clarity with gaming terminology. Consequently, the localization quality is classified as